SoutheAsTern eUrope microciRculATION (SATURATION) registry - Design and rationale - Odanovic, Natalija; Tsioufis, Konstantinos; Dimitriadis, Kyriakos; Sakalidis, Athanasios; Papafaklis, Michail I; Davlouros, Periklis; Ivanov, Igor; Cankovic, Milenko; Kalogeropoulos, Andreas S; Hamilos, Michalis; Sideras, Emmanuel; Konigstein, Maayan; et al. (Cardiovascular revascularization medicine, 2025)
BACKGROUND: A considerable number of symptomatic patients leave the cardiac catheterization lab without a definitive diagnosis for their symptoms because no epicardial stenoses are found. The significance of disorders of coronary microvasculature and vasomotion as the cause of symptoms and signs of ischemia has only recently been appreciated. Today we have a wide spectrum of invasive coronary physiology tools but little is known about when and how these tools are used in clinical practice. STUDY DESIGN AND METHODOLOGY: SoutheAsTern eUrope microciRculATION (SATURATION) registry will study the regional practice of patient selection for coronary function testing, indications, non-invasive ischemia testing, medications, procedural aspects of invasive physiology evaluation, and treatment changes after testing. The registry is expected to include 1600 patients in participating centers in Southeastern Europe from 2024 to 2029, using the thermodilution technique for evaluation of microcirculation. Major adverse cardiovascular events as well as patient-centered outcomes such as burden of angina and quality of life using Seattle Angina Questionnaire (SAQ) and EQ-5D-5L will be recorded. The study will include patients with different stages of coronary artery disease (presence of disease or degree of stenosis) to elucidate the effect of coronary microcirculation on the outcomes in this broad group. CONCLUSION: The registry will provide information regarding the current practice of invasive coronary physiology assessment in populations at high cardiovascular risk in Southeastern Europe. This could lead to a better understanding of coronary microvascular dysfunction and its relationship to various degrees of coronary atherosclerosis together with potential interventions that can be beneficial.
Keywords: Patient Selection; Prognosis; Coronary flow reserve; Predictive Value of Tests; Humans; Index of microvascular resistance; Europe; INOCA; nemoci koronárních tepen; Microcirculation; prognóza; Registries; Coronary Artery Disease; výběr pacientů; mikrocirkulace; Coronary thermodilution; Evropa; koronární cirkulace; Vasospastic angina; Microvascular angina; Coronary Circulation; Multicenter Studies as Topic; výzkumný projekt; registrace; lidé; multicentrické studie jako téma; Quality of Life; prediktivní hodnota testů; Research Design; kvalita života